Evaluation of Neutron Flux in Boron Neutron Capture Therapy for a 10-Year-Old Child with Head and Neck Rhabdomyosarcoma Using Monte Carlo Simulation - Salim, F. M.; Hidayanto, E.; Setiabudi, W.; Arianto, F. (National Research and Innovation Agency, 2025)
Head and neck rhabdomyosarcoma is among the most frequently encountered malignancies in children under the age of 10, necessitating effective treatment modalities with minimal toxicity. Boron Neutron Capture Therapy (BNCT) is recognized as a promising therapeutic alternative in radiotherapy owing to its ability to selectively target malignant cells. The aim of this study was to evaluate the neutron beam quality of a BNCT collimator in a simulation model for the treatment of head and neck rhabdomyosarcoma in a 10-year-old pediatric phantom, using the MCNP 6.2 Monte Carlo method. The simulation included tumor modeling incorporating Gross Tumor Volume (GTV), Clinical Target Volume (CTV), and Planning Target Volume (PTV) to assess neutron flux distribution. The results showed a thermal neutron flux of 5.22 × 10⁹ n cm⁻² s⁻¹, an epithermal neutron flux of 1.22 × 10¹⁰ n cm⁻² s⁻¹, and a fast neutron flux of 5.91 × 10⁷ n cm⁻² s⁻¹. Further analysis indicated that the produced epithermal flux exceeded the minimum standard recommended by the IAEA, and the highest flux was concentrated in the GTV region, suggesting effective tumor targeting. However, the thermal-to-epithermal neutron flux ratio (0.43) remained above the threshold value recommended by the IAEA (≤ 0.05). In conclusion, while the collimator design was capable of delivering a high-quality epithermal neutron beam that selectively targeted the tumor, further optimization of the filter components remains necessary to reduce unwanted thermal flux and enhance therapeutic safety and efficacy.